Benchmark dose and the three Rs. Part II. Consequences for study design and animal use. (August 2014) - Slob, Wout
Abstract OECD test guidelines for standard toxicity studies prescribe (minimal) numbers of animals, but these are not substantiated by a quantitative analysis of the relationship between number of animals and the required performance of the associated study design. This paper provides a general approach of how this relationship may be established and discusses the approach in more detail by focusing on the three typical repeated-dose studies (subacute, subchronic, and chronic). Quantitative results derived from simulation studies, including some new results, are summarized and their consequences for study guidelines are discussed. The currently prescribed study designs for repeated-dose studies do not appear to be sufficient when the NOAEL is used for evaluating the data—the probability of not detecting toxicologically significant effects is high. The ensuing need for increasing the number of animals may be avoided by replacing the NOAEL approach by the BMD approach as it increases the probability of detecting the same effects without increasing the number of animals. Hence, applying the BMD approach will result in a virtual reduction in the number of animals. Further, the BMD approach allows for a real reduction in the number of animals on various grounds. It allows for analyzing combined similar datasets, resulting in an increase in precision, which can be translated in animal reduction while keeping the same precision. In addition, applying the BMD approach may be expected to result in animal reduction in the long run, as it allows for distributing the same number of animals over more doses without loss of precision. The latter will reduce the need to repeat studies due to unfortunate dose location.